POLITICAL THINKING AND ATTITUDE OF RELIGION: STUDY OF POLITICAL RESISTANCE OF KIAI AHMAD RIFA`I KALISALAK AL-JAWI ON COLONIALISM OF THE NETHERLANDS - Abdul Basit Atamimi; Athoillah Islamy (STAIN Bengkalis, 2019)
This study aims to find a form of political resistance of Kiai Ahmad Rifa`i Kalisalak al-Jawi and his followers (Rifa`iyah) against the colonialism of the Dutch East Indies Government in Java in the late 18th century and early 19th century. This study is a qualitative research in the form of library research. This study concludes that the political resistance of the kiai Rifa`i in opposing the Dutch colonial government was only an attempt to engage in anti-government behavior, not with physical resistance. The political thoughts and attitudes of Kiai Rifa`i's resistance were manifested in three things. First, the existence of the Dutch colonial government was a pagan government that was forbidden to obey its policies. Secondly, the traditional bureaucrats, including the headman and ulama who worked with the Dutch, were Dutch minions and they belonged to a group of wicked Muslims. Third, the practice of religion must not be mixed with the beliefs of the ancestors, which are considered heretical and polytheistic.